(untitled) (Comunicação & Inovação, 2016)
The article identifies the role of patients in discussing personal health issues in the digital environment. The innovations offered by the PatientsLikeMe platform create an environment where patients, caregivers and healthcare professionals share questions, suggestions and complaints that, studied qualitatively, can generate information for researchers from the medical field and pharmaceutical companies. The research maps the scientific production indexed using the keyword "PatientsLikeMe" and discusses not only the innovative aspects of the platform, but also the segmented interests and challenges to overcome in the new communicational locus.